2012
DOI: 10.1007/s00421-012-2547-x
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-effects model of the dynamic response of muscle gene transcript expression to endurance exercise

Abstract: Altered expression of a broad range of gene transcripts after exercise reflects the specific adjustment of skeletal muscle makeup to endurance training. Towards a quantitative understanding of this molecular regulation, we aimed to build a mixed-effects model of the dynamics of co-related transcript responses to exercise. It was built on the assumption that transcript levels after exercise varied because of changes in the balance between transcript synthesis and degradation. It was applied to microarray data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Adjustments of mitochondria-associated transcript and protein expression were probed and assessed for linear relationships to cellular and functional variables of oxygen metabolism. The choice of the 24-h time point to assess transcript expression after bicycle exercise was based on the established switch in COX4 isoform expression after 24 h of hypoxia exposure in culture (Fukuda et al 2007), the responsiveness of transcript expression at this time point (Busso and Fluck 2013), and the fact that at this time point the next training session would normally take place. Our study identified hypoxia-specific regulation of the COX4I2 transcript after a single bout of exercise and found that the exercise-induced changes in this transcript also correlated to exercise-induced changes in the transcript for the mitochondria-associated isoform C of lactate dehydrogenase, LDHC, and training-induced changes in volume density of subsarcolemmal mitochondria (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Adjustments of mitochondria-associated transcript and protein expression were probed and assessed for linear relationships to cellular and functional variables of oxygen metabolism. The choice of the 24-h time point to assess transcript expression after bicycle exercise was based on the established switch in COX4 isoform expression after 24 h of hypoxia exposure in culture (Fukuda et al 2007), the responsiveness of transcript expression at this time point (Busso and Fluck 2013), and the fact that at this time point the next training session would normally take place. Our study identified hypoxia-specific regulation of the COX4I2 transcript after a single bout of exercise and found that the exercise-induced changes in this transcript also correlated to exercise-induced changes in the transcript for the mitochondria-associated isoform C of lactate dehydrogenase, LDHC, and training-induced changes in volume density of subsarcolemmal mitochondria (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This result however is critical as pre LCFR values for both CTRL myofiber types are markedly higher than those of the JUMP group. Of note, however, is that while resistance training (Rudnick et al, 2004) and endurance training (ET) (Andersen and Henriksson, 1977;Ingjer, 1979;Hoppeler et al, 1985;Jensen et al, 2004;Schmutz et al, 2010;Busso and Fluck, 2013;Egan and Zierath, 2013) Determination of optical density of SDH marker at 660 nm (OD 660 ) in control (CTRL) (myofiber type I/II n = 6, hybrid pre n = 0 post n = 3 R + 10 n = 4) or exercise (JUMP, VL myofiber type I/II n = 6, hybrid pre n = 4, post n = 2, R + 10 = 3). The specific SDH activity (OD SDH ) was always higher in CTRL pre/post/recovery (R + 10) type I vs. type II myofibers (pre p = 0.028, post p = 0.043, recovery p = 0.014).…”
Section: Capillarizationmentioning
confidence: 99%
“…With the repetition of exercise the consequent elevation in microvascular shear stress stimulates in conjunction with abluminal mechanical factors morphogenic adaptations and proliferation of endothelial cells in muscle capillaries (Bassett and Howley, 2000 ; Gustafsson and Kraus, 2001 ; Prior et al, 2003 ). The consequent adaptations in muscle capillarisation manifest in a typical 20–40% increase in capillary density or capillary-to-fiber ratio after a sufficiently intense and long training stimulus such as exhaustive endurance exercise when sessions are repeated 5 times per week over 4–8 weeks (Hoppeler et al, 1985 ; Schmutz et al, 2010 ; Busso and Flück, 2013 ; Egan and Zierath, 2013 ). Thereby signs of capillary remodeling in exercised muscle are already detectable 3–12 h into recovery from a single exercise session by virtue of altered muscle expression of angiogenesis-associated gene transcripts (Clifford and Hellsten, 2004 ; Egginton, 2009 ; Schmutz et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%